JURNAL KESEHATAN PENGARUH PENDIDIKAN KESEHATAN TINDAKAN KEGAWATDARURATAN TERHADAP KETERAMPILAN PENANGANAN KECELAKAAN LALU LINTAS PADA SISWA SMK MUHAMMADIYAH CAWAS - witri yani (STIKES DUTAGAMA KLATEN, 2022)
Background: Several ways of first aid in traffic accidents, such as moving the victim without regard to the position of the head and neck, are inappropriate first aid. These methods can aggravate the victim's condition, while pre-hospital first aid skills greatly affect the victim while being treated at the hospital. Objective: To determine the influence of health education of emergency actions towards traffic accident handling skills on students of SMK Muhammadiyah Cawas. Research method: this study was experimental research with a one group pre-posttest design. The sampling technique used was purposive sampling. The sample consisted of 24 students. The skills were measured by using a skill observation form as many as 28 actions that must be practiced. Results: Before the intervention the average result was 31.1 and after the intervention the average result was 34. It means that Posttest > Pretest. Then the Wilcoxon test was carried out, the results obtained P-Value = 0.001 (P <0.005) which means that the hypothesis was accepted. Conclusion: there was influence of health education of emergency actions towards traffic accident handling skills on students of SMK Muhammadiyah Cawas.